POLITENESS STRATEGIES ON ORDERING SPEECH ACT - Agustina Aloojaha (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
This research is a translation study on politeness strategies in ordering speech act of novel Christ the Lord out of Egypt and its translation in Indonesian, Kristus Tuhan Meninggalkan Mesir. The purpose of this research is to describe how politeness strategies exist in ordering speech and how politeness strategies impacted the translation qualites. This research used qualitative descriptive method. The data source of the research is the document in the form of the novels namely original novel and translation novel. The data are focused on the sentences that accommodate politeness strategy in ordering speech act. Politeness strategies are known through translation techniques that are used in the novel translation. By analyzing data, it showed that the politeness strategies used in ordering speech act are bald on record, positive politeness, negative politeness, and off record. Based on the data, translation qualities of ordering speech sentences in the novel translation have shifted because of the use of politeness strategies. Furthermore bald on record is more shifted than other because it is shifting into positive politeness. So it can be concluded that the politeness strategies have changed the meaning of ordering speech on source language in English as asking speech on target language in Indonesian.